Aqueous pretreatment of plant biomass for biological and chemical conversion to fuels and chemicals - Wyman, Charles, ....- (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
Plant biomass is attracting increasing attention as a sustainable resource for large-scale production of renewable fuels and chemicals. However, in order to successfully compete with petroleum, it is vital that biomass conversion processes are designed to minimize costs and maximize yields. Advances in pretreatment technology are critical in order to develop high-yielding, cost-competitive routes to renewable fuels and chemicals. Aqueous Pretreatment of Plant Biomass for Biological and Chemical Conversion to Fuels and Chemicals presents a comprehensive overview of the currently available aqueous pretreatment technologies for cellulosic biomass, highlighting the fundamental chemistry and biology of each method, key attributes and limitations, and opportunities for future advances.
Includes index.
Keywords: Plant biomass; Biomass energy; Biomass chemicals; Biotechnology